Peningkatan Pembelajaran Menggunakan Model Kooperatif Tipe Number Head Together di Sekolah Dasar - Hendrizal, Hendrizal; YP, Angga Dwi Pranata (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by the reality in the field which shows the low involvement of students in the learning process, where students are less active and seem not enthusiastic about participating in the learning process. This is because teachers still tend to use teacher-oriented learning when explaining learning, so the integrated thematic learning process is not in line with expectations. The purpose of this study was to describe the use of the Number Head Together model to improve the integrated thematic learning process in the fourth grade of SDN 13 Pancung Question in the Pesisir Selatan Regency. This type of research is classroom action research (CAR) using qualitative and quantitative approaches. This research was conducted in two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The subjects in this study were teachers as observers, researchers as practitioners, and 27 students of class IV SDN 13 Pancung Question. The results of the first cycle of research on RPP obtainedan average percentage value of 76.78% with sufficient qualifications, increasing in the second cycle to 85.71% with good qualifications. The implementation of the first cycle in teacher activities obtained an average percentage value of 78.12% with sufficient qualifications, increasing in the second cycle to 87.5% with good qualifications. The implementation of the first cycle on student activities obtained an average percentage value of 78.12% with sufficient qualifications, increasing in the second cycle to 87.5% with good qualifications. Thus, it can be concluded that the Numbered Head Together learning model can improve the integrated thematic learning process in class IV at SDN 13 Pancung Question in Pesisir Selatan Regency.